Kinerja Ditinjau Dari Teori Mutasi, Iklim Organisasi, Kepemimpinan Transformasional dan Kepuasan Kerja - Yummil Hasan (Hikmah, 2018)
In general, performance is limited as a person's success in performing a job. Performance is one's success in performing the task. Another opinion states that performance is the work achieved by a person or group of persons within an organization, in accordance with their respective powers and responsibilities, in an effort to achieve the objectives of the organization in a legal, unlawful, and moral and ethical manner. Factors that affect performance are conditions, biological and social factors that affect the environment of one's life. This behavior will be brought into his new environment including in personal life.Key word: Performance, mutation, organizational climate, transforma-tional leadership, job satisfaction.